2021 IEEE 34th International Symposium on Computer-Based Medical Systems (CBMS) 2021
DOI: 10.1109/cbms52027.2021.00048
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing Schizophrenia from Activity Records using Hidden Markov Model Parameters

Abstract: The diagnosis of Schizophrenia is mainly based on qualitative characteristics. With the usage of portable devices which measure activity of humans, the diagnosis of Schizophrenia can be enriched through quantitative features. The goal of this work is to classify between schizophrenic and non-schizophrenic subjects based on their measured activity over a certain amount of time. To do so, the periods in which a subject was resting or active were identified by the application of a Hidden Markov model (HMM). The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Their proposed method performed a cut above the rest of the deployed machine learning techniques. Boeker et al 44 proposed hidden Markov model (HMM) parameters to classify healthy controls and schizophrenia patients. The work aimed to classify non-schizophrenic and schizophrenic participants based on the HMM, and the results showed that the features of the HMM were outperforming other models in terms of classifying non-schizophrenic and schizophrenic participants.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their proposed method performed a cut above the rest of the deployed machine learning techniques. Boeker et al 44 proposed hidden Markov model (HMM) parameters to classify healthy controls and schizophrenia patients. The work aimed to classify non-schizophrenic and schizophrenic participants based on the HMM, and the results showed that the features of the HMM were outperforming other models in terms of classifying non-schizophrenic and schizophrenic participants.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To gain a better understanding of the sleep/wake pattern, HMMs can be used to extract these patterns. HMMs have already been applied for this purpose [43,23,44].…”
Section: Related Workmentioning
confidence: 99%
“…Boeker et al [23] applied HMMs to describe the sleep/wake pattern as two states. The HMM parameters are extracted and used as features for logistic regression.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of continuation in receiving data points and the interest in finding hidden states by modeling observable sequential data, HMM is a capable model. HMM has been used in various medical applications [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. Moreover, it has been applied in human activity recognition [ 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ].…”
Section: Introductionmentioning
confidence: 99%